Marine-Derived Bioactive Peptides as New Anticoagulant Agents: A Review - Nasri, Rim; Nasri, Moncef (Current Protein and Peptide Science, 2013)
The development of more effective antithrombotic agents with reduced side risk is necessary for the prevention of thromboembolic events. In recent years, bioactive peptides derived from food proteins have received considerable attention because of their numerous healths beneficial. Based on their amino acids sequences these peptides can exhibit various biological activities including, antihypertensive, antioxidative and antibacterial activities. Moreover, several naturally or food proteins-derived bioactive peptides that could prolong the activated partial thromboplastin time (APTT) and thrombin time (TT) have been isolated. Due to their therapeutic potential in the treatment or prevention of various diseases, bioactive peptides can be used as functional food ingredients, nutraceuticals or pharmaceuticals. Marine organisms represent a valuable source of new bioactive substances including bioactive peptides. This paper presents an overview of the bioactive anticoagulant peptides derived from fish protein sources, as well as the enzymatic proteolysis approach used for the development of these new biopeptides.
Keywords: antithrombotic